Analysis of the Implementation of the Zoning System Policy and its Impact on Islamic Educational Institutions - Halimah, Siti; Damayanti, Putri Elvina; Adawiyah, Robiatul; Nuriya, Sinta; Kholda, Sinta Nuriya (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The growth of Islamic educational institutions in Indonesia faces new challenges and opportunities due to globalization, particularly regarding the implementation of the zoning system in the New Student Admissions (PPDB). This research aims to examine the impact of the zoning system on Islamic educational institutions and to explore the opportunities and obstacles they encounter. The study employs a qualitative approach, utilizing data collection through observations, interviews, and documentation in several Madrasah Aliyah in the Pasuruan City and Regency. The findings reveal that the zoning policy has both positive and negative effects, with Islamic educational institutions experiencing an increase in applicants due to their flexibility in recruiting high-achieving students without geographic restrictions. However, institutions under the Ministry of Education and Culture face declines in applicant numbers. This research provides insights into the effects of the zoning system and the potential for Islamic educational institutions to enhance their appeal and educational quality. It is hoped that the findings will serve as a reference for policymakers and educational administrators in addressing challenges and leveraging opportunities in the era of globalization.